Differential survival of alfalfa varieties interseeded into corn silage. Issue 3 (18th March 2021) - Grabber, John H.; Osterholz, William R.; Riday, Heathcliffe; Cassida, Kimberly A.; Williamson, Jessica A.; Renz, Mark J.
Abstract: Interseeding alfalfa ( Medicago sativa L.) into silage corn ( Zea mays L.) can improve forage yield, farm profitability, and soil conservation, but unreliable alfalfa establishment hampers on‐farm adoption. This study evaluated seedling survival and growth of 36 alfalfa varieties differing in reported plant traits when interseeded at two Wisconsin sites in 2015 and at single sites in Wisconsin, Michigan, and Pennsylvania in 2016. Subplots of alfalfa varieties were sprayed with prohexadione‐calcium (PHD) at 0 or 0.42 kg acid equivalent (a.e.) ha –1 to assess changes in seedling survival mediated by this growth retardant. After corn harvest in 2015, average stand density of varieties in Wisconsin ranged from 15 to 94 plants m –2 without PHD and from 52 to 199 plants m –2 with PHD. Stand density largely determined subsequent first‐cut alfalfa dry matter yield, which ranged from 1.1 to 6.3 Mg ha –1 . After corn harvest in 2016, stand density of varieties averaged across PHD treatments ranged from 113 to 248 plants m –2 in Michigan and Pennsylvania, compared with only 0.5 to 26 plants m –2 in Wisconsin; PHD treatment improved stand density only in Wisconsin but could not ensure adequate establishment under wet conditions that favored vigorous corn growth and foliar disease on alfalfa. Overall, establishment was poorly related to measured or reported alfalfa traits, but '55H94' and hybrids were consistently among the best performing cultivars. Further work is needed to understand seedling survival mechanisms and to develop improved germplasm and production practices to ensure reliable establishment of interseeded alfalfa.